1985
DOI: 10.3109/02844318509052861
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Studies on the Geometry and Stability of the Distal Radio Ulnar Joint

Abstract: In fresh-frozen amputated- and cadaver arm specimens the anatomy and stability of the distal radio ulnar joint were investigated. The articulating surface of the sigmoid notch of the radius and the corresponding surface of the ulnar head facing the sigmoid notch were studied in transverse cryo sections. In each specimen the radius of the curvature of the sigmoid notch was 4-7 mm larger than that of the ulnar head and consequently pronation and supination are combined rotation-sliding movement in the distal rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
152
0
24

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 304 publications
(183 citation statements)
references
References 12 publications
7
152
0
24
Order By: Relevance
“…21,22 Our results are consistent with these observations, but our analysis of forearm rotation did not include measurements beyond 608 of supination or pronation. Ishii et al 23 reported the contact center to shift dorsally in pronation, and palmar in supination in the uninjured DRUJ, which is in contrast to our finding of no appreciable shift during normal forearm rotation.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…21,22 Our results are consistent with these observations, but our analysis of forearm rotation did not include measurements beyond 608 of supination or pronation. Ishii et al 23 reported the contact center to shift dorsally in pronation, and palmar in supination in the uninjured DRUJ, which is in contrast to our finding of no appreciable shift during normal forearm rotation.…”
Section: Discussionsupporting
confidence: 82%
“…However, this description of the role of the radioulnar ligaments is not consistent with the observations of af Ekenstam and Hagert. 21 We found that the computed path lengths for the dorsal radioulnar ligament in the uninjured forearm tended to elongate with pronation. The computed path lengths for palmar radioulnar ligaments in our study tended to be longest in the neutral posture, suggesting it became lax in supination and pronation.…”
Section: Discussionmentioning
confidence: 95%
“…The contact is reduced to less then 10% in maximum supination and pronation. 2,30 For this reason, the osseous anatomy provides only little stability (20%). The main stabilizer of the DRUJ (80%) is the three-dimensionally structured triangular fibrocartilage complex (TFCC), which is located between the ulnar head and the corresponding carpal bones.…”
Section: Anatomy and Biomechanics Of The Drujmentioning
confidence: 99%
“…Besides its main function as a stabilizer of the DRUJ and the ulnocarpal joint, the TFCC also supports the axial load transmission and acts as a buffer. 2,31 Essential structures for DRUJ stability are the palmar and dorsal radioulnar ligaments. These bands arise from the dorsal and palmar edge of the sigmoid notch of the radius.…”
Section: Anatomy and Biomechanics Of The Drujmentioning
confidence: 99%
See 1 more Smart Citation